Risk Factors for Cognitive Impairment in Adult Population of Coastal Area: A Cross-Sectional Study in Maringkik Island, Indonesia - Harahap, Herpan Syafii; Rivarti, Arina Windri; Nurhidayati, Nurhidayati; Zubaidi, Fitriannisa Faradina; Suryani, Dini; Saputri, Legis Ocktaviana; Indrayana, Yanna; Andhera, Athalita; Hilam, Muhammad; Haq, Abiyyu Didar (Kesmas, 2024)
Cognitive impairment is a medical condition commonly found in elderly populations, which can be due to vascular risk factors in patients. There remains limited data on risk factors for cognitive impairment among coastal region populations. This study aimed to investigate risk factors for cognitive impairment in the adult population of Maringkik Island, West Nusa Tenggara Province, Indonesia. Data collected were age, sex, education level, hypertension, antihypertensive treatment, diabetes mellitus, cigarette smoking, and body mass index status. A total of 114 participants were recruited using a consecutive sampling method. The participants’ cognitive function assessment used the Mini-Cog instrument. The cognitive impairment frequency in the island’s adult population was approximately 48.2%. The final model of multiple regression analysis showed that hypertension (OR: 2.3; 95%CI: 1.0 – 5.0; p-value: 0.045) was a characteristic associated with the cognitive impairment frequency. Thus, the high frequency of cognitive impairment and hypertension frequency as primary risk factors for cognitive impairment in the island’s adult population implies the need to develop strategies for detecting and managing hypertension and hypertension-related cognitive impairment in the population by local health authorities.